2020
DOI: 10.1007/s42770-020-00260-x
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic characterization of bacterial biofilm in four food processing plants in Colombia

Abstract: Bacteria inside biofilms are more persistent and resistant to stress conditions found in the production environment of food processing plants, thus representing a constant risk for product safety and quality. Therefore, the aim of this study was to characterize, using 16S rRNA sequencing, the bacterial communities from biofilms found in four food processing plants (P1, P2, P3, and P4). In total, 50 samples from these four processing plants were taken after cleaning and disinfection processes. Four phyla: Prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…Moreover, the genus Leuconostoc was found in the four sampled surfaces, validating the cross-contamination product-surfaces-product. These results are concordant with the study on meat products factories reported by Caraballo Guzmán et al (2020) , where Proteobacteria represent 51.7% and 45.4% of OTUs of two factories. Along with that, the family Alyciclobacillus was found in occurrences of 66.6% and 33.3% for both meat factories, and the genus Acinetobacter had the highest occurrences due to persistence and survival ability on facility environments.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, the genus Leuconostoc was found in the four sampled surfaces, validating the cross-contamination product-surfaces-product. These results are concordant with the study on meat products factories reported by Caraballo Guzmán et al (2020) , where Proteobacteria represent 51.7% and 45.4% of OTUs of two factories. Along with that, the family Alyciclobacillus was found in occurrences of 66.6% and 33.3% for both meat factories, and the genus Acinetobacter had the highest occurrences due to persistence and survival ability on facility environments.…”
Section: Resultssupporting
confidence: 92%
“…Bacterial identity was determined by NGS techniques using the Miseq Illumina platform (Illumina, San Diego, USA), targeting the V4 region of the 16S rRNA gene. Metagenomic profiles based on amplicons of bacterial communities and their composition analysis were performed under protocols proposed by Caraballo Guzmán et al (2020) . The number of observed OTUs and alpha diversity metrics were calculated as Chao1, Heip, and Shannon indexes for ham treatments.…”
Section: Methodsmentioning
confidence: 99%
“…However, the analysis of similarities suggested that PA bacterial communities of the control and olivine-added groups were different after 10 days of incubation. The interaction between olivine particles and biofilm-forming microbes was considered the main reason for changes in PA bacterial community composition ( Shirokova et al, 2012 ; Caraballo Guzman et al, 2020 ). Phyla Bacteroidota and Firmicutes have an inclination for growth attached to particles ( Fernandez-Gomez et al, 2013 ; Zhang et al, 2016 ; Bachmann et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since all these genera are also highly abundant and include species that are frequently described as spoilage organisms, the widespread establishment of these bacteria throughout the facility is (Odeyemi et al, 2020). In another study, bacterial communities from biofilms in four FPEs were characterized by 16S rRNA gene sequencing: Proteobacteria, Firmicutes, Actinobacteriota, and Bacteroidota represented over 94% of the operational taxonomic units, and Pseudomonas and Acinetobacter were the most dominant genera (93.47%;Caraballo Guzmán et al, 2020). Pseudomonas and Acinetobacter were the most frequently isolated genera surviving on conveyor belts after cleaning and disinfection in meat processing plants (Fagerlund et al, 2017).…”
Section: Discussionmentioning
confidence: 99%